Survival of two dogs with pyothorax secondary to perforating oesophageal foreign body. Issue 1 (January 2017) - Boyd, C; Claus, M; Hosgood, G; Smart, L
Abstract : Case report: Two dogs with an oesophageal foreign body (FB) were diagnosed with secondary pyothorax at the time of presentation. One dog was managed with surgical FB removal, pleural lavage and thoracostomy tube placement. Following surgery, it was admitted to the intensive care unit for oxygen therapy, antimicrobial and analgesic administration, fluid therapy, thoracic drainage and enteral nutrition. The other dog was managed with endoscopic FB removal, thoracostomy tube placement with continuous suction, and similar aftercare in the intensive care unit. Both survived to discharge from hospital. Conclusion: This report details the treatment and survival of two dogs with secondary pyothorax associated with oesophageal FB, with successful management through supportive care, oesophageal rest and treatment of infection.